الثمن في عقود التجارة الدولية - أمــــــــــــال عــــــــزاق; ريــــــــــهـــــــان كحايليــــــــة (My University, 2019)
Summary: This research addresses the subject of insurance in international trade contracts where the international sales contract imposes on the parties a number of obligations, the most important of which are to pay the price for obtaining the sale in terms of its content or in terms of how it implements many conflicts between its parties, Uniform international law has sought to establish a set of legal norms, most of which are complementary to the contractors' will, but which are particularly important in the absence of agreement between the parties or in the event of a dispute between them. .......................... ملخـــــــص يعالج هذا البحث موضوع التمن في عقود التجارة الدولية حيث نجد ان عقد البيع الدولي يفرض على الاطراف عدد من الالتزامات اهمها دفع الثمن مقابل الحصول على المبيع، حيث محتواه أو من حيث كيفية تنفيذه العديد من النزاعات بين اطرافه، وقد سعى القانون الدولي الموحد الى وضع مجموعة من القواعد القانونية التي في أغلبها قواعد مكملة بإرادة المتعاقدين لكن تظهر اهميتها خاصة عند غياب الاتفاق بين الطرفين أو في حالة وقوع نزاع بينهما. ...................... Résumé : Cette recherche aborde la question de l’assurance dans les contrats de commerce international lorsque le contrat de vente internationale impose aux parties un certain nombre d’obligations, dont les plus importantes sont de payer le prix d’obtention de la vente en termes de contenu ou en termes de mise en œuvre de nombreux conflits entre ses parties, le droit international uniforme a cherché à établir un ensemble de normes juridiques, dont la plupart sont complémentaires à la volonté des contractants, mais qui sont particulièrement importantes en l’absence d’accord entre les parties ou en cas de litige entre elles.